T1-Weighted Dynamic Contrast-Enhanced MR Evaluation of Different Stages of Neurocysticercosis and Its Relationship with Serum MMP-9 Expression - Gupta, R.K.; Awasthi, R.; Garg, R.K.; Kumar, N.; Gupta, P.K.; Singh, A.K.; Sahoo, P.; Paliwal, V.K.; Prasad, K.N.; Pandey, C.M.; Rathore, R.K.S. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Epileptogenesis in NCC is associated with perilesional inflammation and disruption in BBB. We quantified BBB in different stages of NCC by using DCE-MR imaging to look for the differences in perfusion indices and to correlate these indices with serum MMP-9 expression. MATERIALS AND METHODS: DCE-MR imaging along with conventional MR imaging was performed in 57 single cysticercous brain lesions to quantify the kep, Ktrans, and ve around the lesions, which were in different stages of evolution. There were 6 lesions in the vesicular stage and 17 lesions each in the colloidal, granular-nodular, and calcified stages. Serum MMP-9 was quantified from all patients, whereas perfusion indices were quantified from all stages except for the vesicular stage. RESULTS: We observed significant differences among the 3 stages of NCC in serum MMP-9 expression as well as DCE-derived kep values. In addition, kep showed a strongly significant positive correlation with MMP-9 expression when modeled with the individual stage of the disease as well as with all stages when pooled together. Other DCE-derived hemodynamic and pharmacokinetic parameters showed inconsistent differences with each stage of the disease. The correlation of DCE-derived parameters with serum MMP-9 expression and edema volume also showed inconsistency with the stage of the disease. CONCLUSIONS: We conclude that kep correlates best with serum MMP-9 expression among the pharmacokinetic indices and most closely represents the degree of BBB breakdown, which is highest in the colloidal stage and lowest in the calcified stage. kep may be used as a noninvasive image biomarker of BBB breakdown in different stages of NCC. keprate transfer constantKtransvolume transfer coefficientDCEdynamic contrast-enhancedMMPmatrix metalloproteinaseNCCneurocysticercosisveleakage volume